Relapsed follicular lymphoma sequentially treated with rituximab and 90Y-ibritumomab tiuxetan. Case report - Papajik, Tomas; Prochazka, Vit; Raida, Ludek; Kubova, Zuzana; Myslivecek, Miroslav; Drymlova, Jaroslava; Buriankova, Eva; Kucerova, Ladislava; Indrak, Karel (Biomedical papers, 2007)
Background: Monoclonal antibodies have dramatically changed the treatment possibilities for follicular lymphoma. 90Y-ibritumomab tiuxetan (Zevalin(R)) is the first radioimmunotherapy agent approved for the treatment of relapsed and resistant follicular lymphoma patients. Long-term benefit was observed especially for patients achieving CR after radioimmunotherapy.Methods and Results: A 65-year-old female patient with the second relapse of CD20 positive follicular lymphoma and multiple concomitant diseases was treated with four weekly doses of rituximab (375 mg/m2). 18F-fl uoro-deoxyglucose positron emission tomography combined with computed tomography (PET-CT) demonstrated only partial response to therapy with persistent PET scan positivity in enlarged abdominal lymph nodes. Therefore, it was decided to treat her with a 1200-MBq (32-mCi) dose of 90Y-ibritumomab tiuxetan radioimmunotherapy. No acute complications were noted afterwards. Hematological nadirs were reached 4 weeks later, with a platelet count of 24x109/l that normalized within the next 2 weeks. The patient had neither infection nor bleeding complications. Eight weeks after radioimmunotherapy, the PET-CT scans documented only 3 lymph nodes around the abdominal aorta, maximum size 2x1 cm. The PET scan analysis proved no accumulation of 18F-fluoro-deoxy-glucose in any lymph nodes or other organs and tissues.Conclusions: Sequential treatment with rituximab and 90Y-ibritumomab tiuxetan may be an interesting alternative in cases of relapsed follicular or other indolent lymphomas in pretreated or older patients with other concomitant diseases.
Keywords: Follicular lymphoma/Ibritumomab tiuxetan/Rituximab/CD20 antigen/Therapy/Positron emission tomography